St. Gallen 2011: Summary of the Consensus Discussion - Gnant, Michael (S. Karger GmbH, 2011)
SUMMARY: The 2011 St. Gallen Consensus Conference on early breast cancer provided mostly evidence-based treatment recommendations with a broad spectrum of acceptable clinical practice for global breast cancer care. This report summarizes the results of the 2011 international panel voting procedures with regard to locoregional and endocrine treatment, chemotherapy, targeted therapy as well as adjuvant bisphosphonate use.